Towards an exposure-dependent model of post-traumatic stress: longitudinal course of post-traumatic stress symptomatology and functional impairment after the 2011 Oslo bombing. Issue 15 (9th September 2016) - Solberg, Ø.; Birkeland, M. S.; Blix, I.; Hansen, M. B.; Heir, T.
Abstract : Background: Our understanding of the dynamics of post-traumatic stress symptomatology and its link to functional impairment over time is limited. Method: Post-traumatic stress symptomatology (Post-traumatic Checklist, PCL) was assessed three times in 1-year increments (T1, T2, T3) following the Oslo bombing of 22 July, 2011, in directly ( n = 257) and indirectly exposed ( n = 2223) government employees, together with demographics, measures of exposure and work and social adjustment. The dynamics of post-traumatic stress disorder symptom cluster interplay were examined within a structural equation modelling framework using a cross-lagged autoregressive panel model. Results: Intrusions at T1 played a prominent role in predicting all symptom clusters at T2 for the directly exposed group, exhibiting especially strong cross-lagged relationships with avoidance and anxious arousal. For the indirectly exposed group, dysphoric arousal at T1 played the most prominent role in predicting all symptom clusters at T2, exhibiting a strong relationship with emotional numbing. Emotional numbing seemed to be the main driver behind prolonged stress at T3 for both groups. Functional impairment was predominately associated with dysphoric arousal and emotional numbing in both groups. Conclusions: For directly exposed individuals, memories of the traumatic incident and the following intrusions seem to drive their post-traumatic stress symptomatology. However, as these memories lose their potency over time, a sequela of dysphoric arousal and emotional numbing similar to the one reported by the indirectly exposed individuals seems to be the main driver for prolonged post-traumatic stress and functional impairment. Findings are discussed using contemporary models within an exposure-dependent perspective of post-traumatic stress.